Economics of Lentil Production under Relay and Conventional Tillage Practice - Poudel, Hema K.; Timsina, Krishna P.; Adhikari, Surya P.; Devkota, Deepa; Subedi, Sanjiv; Kharel, Meena; Giri, Rabin; Bohara, Suman; Upadhyaya, Jharana; Poudel, Mukti R. (Agriculture Development Journal, 2022)
The study was intended to find out the most profitable method between the relay and tillage growing method of lentil production. For primary data collection, a simple random sampling method was followed. Household survey was conducted in two districts Bardiya and Kailali in 2021 AD. A total of 107 lentil farmers (43 farmers following relay and 64 farmers following tillage practices) were randomly selected from two pockets area (relay and tillage method adopters) of each district. Benefit-Cost (BC) ratio analysis was done to find out the most profitable method of lentil cultivation. Multiple regression model was applied to estimate the factors determining the lentil production. The average BC ratio is 2.18 which indicates that lentil cultivation is profitable with average productivity of 0.64 mt/ha. The total cost incurred per ha in relay and tillage method was NRs. 24345 and NRs. 33549 respectively. Similarly, gross income from relay and tillage method was found NRs. 56160 and NRs 69870, per ha respectively. In between the two popular methods (relay and tillage) of lentil cultivation, the BC ratio was found 2.31 in the relay method compared to 2.08 in the tillage method. Among the several socio-economic independent variables used in the model, the age of the household head and fertilizer application significantly influenced the lentil production. However, lentil production is negatively affected by the practice of intermixed cropping. Hence the result indicates that relay cropping with mono-cropping and appropriate management of fertilizer could play a crucial role to boost the profitability of lentil farming